IDENTIFICATON OF UNIT SHIFT FROM WORD TO PHRASE IN ENGLISH-INDONESIAN TRANSLATION OF MS WIZ SPELLS TROUBLE BY TERENCE BLACKER - Naufal, Muhammmad (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2019)
The research entitled â€œIdentification of Unit Shift from Word to Phrase in English-Indonesian Translation of Ms Wiz Spells Trouble by Terence Blackerâ€ finds the unit shift and classifies the unit shift in Ms Wiz Spells Trouble short stories by Terrence blacker. The theory used in this research is unit shift by Catford as seen in his book entitled â€˜A Linguistic Theory of Translationâ€™. Descriptive analysis method is used to analyze the data in the research. Based on the analysis, unit shift is a change of a unit in source language to a different unit in target language. There are two classified unit shift in the research; from Adverb to adverbial phrase and adjective to adjective phrase.